PRE-SERVICE TEACHERS' PERCEPTIONS AND INSTRUCTIONAL PRACTICES OF EFL LEARNING STRATEGIES - Egi Fajriyandi, - (2018)
In the practice of teaching English as a foreign language (EFL), it is inevitable that EFL teachers do not provide students with learning opportunities. To tackle the aforementioned issue, teachers need to bring EFL learning strategies and teach their students how to use them. Unfortunately, studies about language learning strategies (LLS) involving EFL teachers, very specifically pre-service teachers, are still under-researched. To fill this gap, this present study employing a multiple case study examines the pre-service teachers' perceptions of EFL learning strategies and how they practiced the strategies in their English classrooms. Three participants taking their teaching practicum program in two different Junior High Schools were involved in this research. The data were collected through SILL questionnaires, semi-structured interview, and classroom observations. The results demonstrated that perceptions of EFL learning strategies influenced the instructional practices. Cognitive (practicing and repeating), memory (applying images, reviewing, and employing action), and metacognitive strategies (paying attention to other learners) were indicated to help the students enhance their English ability. Nonetheless, the teaching practices of EFL learning strategies lack explicit strategy intervention, as there were no any explanation about the purpose of language task and selected strategy evaluation. ;---Dalam praktik pembelajaran bahasa Inggris, aktivitas kelas yang berpusat pada guru masih terjadi di berbagai jenjang pendidikan. Untuk mengubah paradigma pembelajaran tersebut, guru perlu membekali siswa dengan berbagai strategi belajar bahasa Inggris dan metode penerapannya. Namun, literatur yang memuat penelitian tentang strategi pembelajaran bahasa Inggris inimasih minim, terutama penelitian yang melibatkan guru praktikan sebagai objek penelitian. Oleh karena itu, penelitian yang menggunakan metode studi kasus ini dilaksanakan untuk menginvestigasi persepsi dari guru praktikan mengenai strategi pembelajaran bahasa Inggris dan penerapan pengajarannya di kelas. Penelitian ini melibatkan 3 orang mahasiswa yang sedang mengikuti program pengalaman lapangan di dua SMP Negeri Bandung yang berbeda. Penelitian ini memanfaatkan penggunaan kuesioner SILL, wawancara semi-structured, dan observasi kelas untuk mengumpulkan data yang dibutuhkan. Hasil dari penelitian ini menunjukkan bahwa penerapan pengajaran strategi pembelajaran bahasa Inggris di kelas sangat dipengaruhi oleh persepsi seorang guru terhadap strategi tersebut. Ada 3 strategi yang paling sering diajarkan oleh guru praktikan karena strategi tersebut dapat membantu siswa untuk meningkatkan kemampuan bahasa Inggrisnya, yaitu strategi kognitif, memori, dan metakognitif. Dari hasil penelitian ini juga ditemukan bahwa pengajaran strategi pembelajaran bahasa Inggris masih bersifat implisit, artinya tidak ada penjelasan mengenai tujuan dari aktivitias pembelajaran dan evaluasi terhadap strategi yang digunakan untuk mengerjakan aktivitas tersebut.